Inter-plant variation of grain yield components and kernel composition of maize crops grown under contrasting nitrogen supply - Mayer, Luis Ignacio (2012)
High intra-specific competition pressure, which is common at most maize (Zea mays L.) cropping conditions, promotes inter-plant variation and the appearance of extreme plant hierarchies with different ability to capture scarce resources (i.e., dominant and dominated plants) within a stand. The objectives of the current work were to analyze (i) inter-plant variation of grain yield per plant (GYP), GYP components (KNP: kernel number per plant; KW: kernel weight), and kernel composition, together with those of their physiological determinants, i.e., plant growth (PG) rate around silking (PGRS), PGRS per kernel (PGRSKNP-1) and PG during the effective grain-filling period per kernel (PGGFKNP-1), under contrasting N supply and (ii) the contribution of dominant and dominated plants to changes in inter-plant variation and mean values of the studied traits. For these purposes two maize hybrids previously characterized by their contrasting inter-plant variation under N stress (low: AX820 and high: AX877) were cultivated at high stand densities (9 and 12plm-2) at two N supplies (N0: control and N200: 200kgNha-1) without water restrictions. For AX820, PGRS data set at both N levels explored a similar range (1-7.4 and 1.2-7.4gpl-1d-1 for N0 and N200, respectively) with a positive skewness in N0, and an almost normal distribution of data in N200. In contrast, for AX877, inter-plant variation of PGRS exhibited a normal distribution in both N levels, and N fertilization only produced a displacement of data to higher PGRS values (0-4.3 and 0.7-5.7gpl-1d-1 for N0 and N200, respectively). The effect of inter-plant variation of PGRS on the coefficient of variation (CV) of KNP was of a greater magnitude in AX877 than in AX820 due to the more linear KNP response to PGRS of the former. For both hybrids, mean values of KW increased and the CVs decreased in response to high N supply. Differences among plants and N levels in KW were related to the duration of the effective grain-filling period. Inter-plant variation of protein and starch concentrations was higher in N0 than in N200, but that of oil concentration was not affected by N supply. The analysis of plant hierarchies resulted useful to understand changes in mean values and frequency distributions of several agronomic traits. © 2011 Elsevier B.V.